The Influence Of Work Discipline And Work Motivation On The Job Satisfaction Of Cipatat Negeri 1 High School Teachers - Maulina, Tyara Puspa; Lestari, Dian (SEAN Institute, 2024)
This research aims to (1) To determine the work discipline of teachers at SMA Negeri 1 Cipatat. (2) To determine the work motivation of teachers at SMA Negeri 1 Cipatat. (3) To determine teacher job satisfaction at SMA Negeri 1 Cipatat. (4) To determine the influence of work discipline and work motivation on teacher job satisfaction, both partially and simultaneously at SMA Negeri 1 Cipatat. The method used in this research is a quantitative method. From this research, it was concluded that the respondents' responses to work discipline at SMA Negeri 1 Cipatat were included in the HIGH criteria. Respondents' responses to work motivation at SMA Negeri 1 Cipatat are included in the VERY HIGH criteria. Respondents' responses to job satisfaction at SMA Negeri 1 Cipatat are included in the VERY SATISFIED criteria. The influence of work discipline and work motivation on job satisfaction at SMA Negeri 1 Cipatat both partially and simultaneously.